Fatigue and cognition: Pupillary responses to problem‐solving in early multiple sclerosis patients. Issue 7 (17th May 2017) - de Rodez Benavent, Sigrid A.; Nygaard, Gro O.; Harbo, Hanne F.; Tønnesen, Siren; Sowa, Piotr; Landrø, Nils I.; Wendel‐Haga, Marte; Etholm, Lars; Nilsen, Kristian B.; Drolsum, Liv; Kerty, Emilia; Celius, Elisabeth G.; et al.
Abstract: Introduction: In early multiple sclerosis (MS) patients, cognitive changes and fatigue are frequent and troublesome symptoms, probably related to both structural and functional brain changes. Whether there is a common cause of these symptoms in MS is unknown. In theory, an altered regulation of central neuropeptides can lead to changes in regulation of autonomic function, cognitive difficulties, and fatigue. Direct measurements of central neuropeptides are difficult to perform, but measurements of the eye pupil can be used as a reliable proxy of function. Methods: This study assesses pupil size during problem‐solving in early MS patients versus controls. A difference in pupil size to a cognitive challenge could signal altered activity within the autonomic system because of early functional brain changes associated with cognitive load. We recruited MS patients (mean disease duration: 2.6 years, N = 41) and age‐matched healthy controls ( N = 43) without eye pathology. Neurological impairment, magnetic resonance imaging, visual evoked potentials, depression, and fatigue were assessed in all of the patients. In both groups, we assessed processing speed and retinal imaging. Pupil size was recorded with an eye‐tracker during playback of multiplication tasks. Results: Both groups performed well on the cognitive test. The groups showed similar pupillary responses with a mean of 0.55 mm dilation in patients and 0.54 mm dilation in controls for all the tasks collapsed together. However, controls ( N = 9) with low cognitive scores (LCS) had an increased pupillary response to cognitive tasks, whereas LCS MS patients ( N = 6) did not ( p < .05). There was a tendency toward a smaller pupillary response in patients with fatigue. Conclusions: This is the first study to investigate pupillary responses to cognitive tasks in MS patients. Our results suggest that MS‐related changes in cognition and fatigue may be associated with changes in arousal and the autonomic regulation of task‐related pupillary responses. This supports the theory of a link between cognition and fatigue in MS. Abstract : This is the first study to investigate pupillary responses to cognitive tasks in MS patients. Our study points toward an altered locus Coeruleus's response in MS patients with symptoms of fatigue. We propose pupillometry as a valid method for unveiling task‐related changes of attention that may link cognition and fatigue.